Campus Canopy, 1937-10-02 - The Campus Canopy, The Georgia State Woman's College (Georgia State Womans College, 1937)
"Y" Sponsors Sophomore Council Work -- Sock and Buskin Club Extends Membership To Tryout Winners -- A.D. Fraternity Teaches Writing To Reporters -- SGA Centers Around New Classmen -- Reade Explains Important Rules For Attendance -- Dean Releases Class Honor Roll -- Congresmen Deen Gives Interview To Frightened Freshmen Reporter -- Faculty Honor Student Body at Reception
Georgia State Womans College Student Newspaper
Keywords: Valdosta State University -- Periodicals